ステレオ ガゾウ ヲ モチイタ オーロラ ケイジョウ ノ スイテイ シュホウ ニ ツイテ - 薮, 哲郎; ヤブ, テツロウ; 麻生, 武彦; アソ, タケヒコ; 橋本, 岳; ハシモト, タケシ; 安陪, 稔; アベ, ミノル; 江尻, 全機; エジリ, マサキ; Yabu, Tetsuro; Aso, Takehiko; et al. (1993)
P(論文) 我々は1987年以降, 他に先駆けてオーロラ観測画像よりオーロラの三次元的発光形状を求める研究を行っており, その解析手法としてモデル関数法を用いてきた。モデル関数法とはオーロラを適当な関数によって表し, その関数を構成するパラメータを求めることにより, オーロラの発光形状を推定する手法である。これまでに使用してきたモデル関数は磁気東西方向に一様なオーロラアークを表すものを基本とし, これにアークの曲がりを考慮したものであった。すなわち, アークの断面における二次元の発光分布をオーロラの厚み方向の明るさ分布を与える関数と高度方向の明るさ分布を与える関数の積で表し, オーロラの伸びる方向には比較的簡単な発光形態を呈することを仮定していた。これに対して本論文では, 三次元的により複雑な形状をしたオーロラを表現するために改良したモデル関数の構成法について詳述する。本論文で提示するモデル関数は, オーロラを各磁力線に沿って地平面に投影した時の投影像を表す二次元の関数と, 高度方向の明るさ分布を表す関数の積により表される。この改良されたモデルを使用することにより, 複雑な曲がりを持ったオーロラアークや不規則な形をしたパルセーティングオーロラについても形状推定が可能になった。本論文ではこれを用いて, アイスランドで観測されたオーロラアークの画像および南極で観測されたパルセーティングオーロラの画像について形状推定を行い, その発光形状を明らかにする。また同時に, 高度方向の発光分布を表す関数形についても検討を行う。 We have been studying reconstruction of auroral 3-D luminous structure from stereo images. We have used the model function method for this problem. In this method, auroral structure is expressed by an appropriate function with some parameters, which are determined by iterative calculations. The auroral model assumes sheet-like luminosity structure with some prescribed thickness and altitude distributions. In this paper, we present an upgraded model function which can express an aurora of more complicated structure. The upgraded model is expressed by the product of a 2-D function which represents projections of an aurora along the geomagnetic lines of force onto the horizontal plane and an altitude function along the geomagnetic line of force. Using this model, curved aurora arcs and pulsating auroras of irregular form can be more properly delineated. In this paper, we analyze the aurora arc observed in Iceland and a pulsating aurora observed in Antarctica. At the same time, we examine the appropriateness of the functional form which expresses the altitude profile of the luminosity of aurora based on theoretical prediction. departmental bulletin paper